2000
DOI: 10.1074/jbc.m909861199
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Parathyroid Hormone

Abstract: The amino-terminal and carboxyl-terminal portions of the 1-34 fragment of parathyroid hormone (PTH) contain the major determinants of receptor activation and receptor binding, respectively. We investigated how the amino-terminal signaling portion of PTH interacts with the receptor by utilizing analogs of the weakly active fragment, rat (r) PTH(1-14)NH 2 , and cells transfected with the wild-type human PTH-1 receptor (hP1R-WT) or a truncated PTH-1 receptor which lacked most of the amino-terminal extracellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 42 publications
6
103
1
Order By: Relevance
“…Consistent with these mutational data, Bpa introduced at position 1 of PTH- or position 2 of either PTH- or PTHrP-(1-36) was found to cross-link to methionine 425, at the extracellular end of TM6 in the P1R (9,10). Interactions between the aminoterminal portion of the ligand and the transmembrane domains/extracellular loops of the receptor are also suggested by a study showing that PTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) can stimulate cAMP accumulation in a mutant P1R missing most of the amino-terminal extracellular domain as efficiently as it does in the wild-type P1R (11). Furthermore, if a PTH fragment comprising the first 9 amino acids is covalently attached to the amino-terminal end of such a truncated receptor, the resulting ligand-receptor chimera displays constitutive activity, indicative of an intramolecular stimulation of the receptor's activation domain by the tethered ligand fragment (12).…”
supporting
confidence: 70%
“…Consistent with these mutational data, Bpa introduced at position 1 of PTH- or position 2 of either PTH- or PTHrP-(1-36) was found to cross-link to methionine 425, at the extracellular end of TM6 in the P1R (9,10). Interactions between the aminoterminal portion of the ligand and the transmembrane domains/extracellular loops of the receptor are also suggested by a study showing that PTH- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) can stimulate cAMP accumulation in a mutant P1R missing most of the amino-terminal extracellular domain as efficiently as it does in the wild-type P1R (11). Furthermore, if a PTH fragment comprising the first 9 amino acids is covalently attached to the amino-terminal end of such a truncated receptor, the resulting ligand-receptor chimera displays constitutive activity, indicative of an intramolecular stimulation of the receptor's activation domain by the tethered ligand fragment (12).…”
supporting
confidence: 70%
“…This analogue has a helix-bend-helix structure in aqueous media at near-physiological pH and ionic strength (14), similar to that found in previous studies of PTH-(1-34) (13). A C-terminal amphiphilic ␣-helix, extending from Ser 17 to Gln 29 , is the major structure within this receptorbinding region, and this structure is thought to bind via its hydrophobic face to the receptor (21)(22)(23). Thus, binding and AC-stimulating activities are very sensitive to replacement of residues on the nonpolar face of this helix, including Leu 24 , Leu 28 , and to a lesser extent Val 31 , whereas residues on the polar face are less sensitive to substitution (22,24).…”
supporting
confidence: 63%
“…A deletion analogue of the P1R (P1R-delNT) that lacks the N-terminal domain (Ref. 16 and citations, therein) can activate the AC and PLC signaling pathways on stimulation with PTH-(1-34) (17), although with much reduced potency, whereas N-terminal PTH analogues as short as PTH-(1-11) exhibit equivalent potencies on P1R-delNt and the intact P1R (16,17). The presence of PLC-independent protein kinase C activity determinants in the C-terminal region of PTH- implies that this region also binds to the extracellular loop/transmembrane domain region of the receptor, but only one report directly supports such an interaction (18).…”
mentioning
confidence: 99%
“…Extensive studies have demonstrated that [Aib 1,3 , M]PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and other PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) analogs (8,(19)(20)(21) mainly, if not exclusively, bind to the PTHR J-domain in contrast to PTH(1-34), which binds to both receptor's N-and J-domains (22). When [Aib 1,3 , M]PTH (1-14) is bound, it prevents PTH analogs from occupying their binding site at the J-domain of the receptor (8,18).…”
Section: Two-mentioning
confidence: 99%